Pragmatic, Semantic and Sociopolitical Facets in TV News Subtitling: A Critical Discourse Analysis of American Televised Interviews in The Real News Network - Farahi, Merzouk (International Journal of Language and Literary Studies, 2024)
Audiovisual translation has gained substantial attention over the past decade. Subtitling has played dynamic roles for all multimedia outlets, connecting narratives to a diverse global audience and allowing worldwide people to enjoy the same audiovisual experience. The current study focuses on a comprehensive scrutiny of pragmatic, semantic, and sociopolitical facets of televisual news interviews in ‘The Real News Network’ (2011-2012). The first underscores the political rift within the Democratic Party as well as between the Democrats and the Republicans while the second accentuates the presumed war on Iran trying to build a nuclear facility. The study aims to identify the effect of conversational implicature, cohesion, coherence, deixis, ambiguity, and figurative interpretation on the conveyance of connotative meaning in context, seeking to investigate the fluently elusive nature of news statements wherein ideologically bound microscopic language is operative. Part of the analysis equally aims to control the intricate hindrances encountered in the subtitling process. The study investigates the way cognitive, social, and ideological dimensions function in the process of subtitling TV news, adopting a critical discourse analysis method (Van Dijk, 1998). The data of the study which comprise a corpus of the interviews’ script and 379 subtitles were analysed to unveil the power of the devices implemented to accurately convey the intended beliefs. The findings which showed noteworthy discrepancies between the source and intended utterances can be valuable for audiovisual translators at large and for news subtitling specialists in particular.